2022
DOI: 10.1021/acs.chemrestox.2c00231
|View full text |Cite
|
Sign up to set email alerts
|

Shared Clavulanate and Tazobactam Antigenic Determinants Activate T-Cells from Hypersensitive Patients

Abstract: β-Lactamase inhibitors such as clavulanic acid and tazobactam were developed to overcome β-lactam antibiotic resistance. Hypersensitivity reactions to these drugs have not been studied in detail, and the antigenic determinants that activate T-cells have not been defined. The objectives of this study were to (i) characterize clavulanate-and tazobactam-responsive Tcells from hypersensitive patients, (ii) explore clavulanate and tazobactam Tcell crossreactivity, and (iii) define the antigenic determinants that co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 35 publications
(69 reference statements)
0
2
0
Order By: Relevance
“…In this sense, recent studies have shown the relevance of the inclusion of different determinant antigens for the detection of drug sIgE to cephalosporins, carbapenems and monobactams 34,35 as well as the beta-lactamase inhibitors clavulanic acid (CLV) 36,37 and tazobactam. 38 All these findings suggest the need to include different antigenic structures in the same assay for diagnosing the maximal number of patients, ensuring the detection of different patterns of recognition. On the other hand, great efforts are being made in the implementation of more sensitive detection methods by using ultra-sensitive chemiluminescence immunoassay, 39 and a multiplex microimmunoassay, 40 with traditional cellulose discs (83% for AX, 78% for BP), and interestingly, the detection of false-positive results of BP sIgE for confirmed AX-selective patients decreased from 41% for cellulose discs to 0% for nanoparticles.…”
Section: Identification Of Ige-mediated Idhrs Is Mainly Based On Skin...mentioning
confidence: 99%
See 1 more Smart Citation
“…In this sense, recent studies have shown the relevance of the inclusion of different determinant antigens for the detection of drug sIgE to cephalosporins, carbapenems and monobactams 34,35 as well as the beta-lactamase inhibitors clavulanic acid (CLV) 36,37 and tazobactam. 38 All these findings suggest the need to include different antigenic structures in the same assay for diagnosing the maximal number of patients, ensuring the detection of different patterns of recognition. On the other hand, great efforts are being made in the implementation of more sensitive detection methods by using ultra-sensitive chemiluminescence immunoassay, 39 and a multiplex microimmunoassay, 40 with traditional cellulose discs (83% for AX, 78% for BP), and interestingly, the detection of false-positive results of BP sIgE for confirmed AX-selective patients decreased from 41% for cellulose discs to 0% for nanoparticles.…”
Section: Identification Of Ige-mediated Idhrs Is Mainly Based On Skin...mentioning
confidence: 99%
“…Moreover, in‐house methods, mostly using radiolabeled anti‐IgE, are indispensable to overcome sensitivity limitations of the fluoroimmunoassays and analyse the immunological recognition of new chemical structures. In this sense, recent studies have shown the relevance of the inclusion of different determinant antigens for the detection of drug sIgE to cephalosporins, carbapenems and monobactams 34,35 as well as the beta‐lactamase inhibitors clavulanic acid (CLV) 36,37 and tazobactam 38 . All these findings suggest the need to include different antigenic structures in the same assay for diagnosing the maximal number of patients, ensuring the detection of different patterns of recognition.…”
Section: Biomarkers In Ige‐mediated Reactionsmentioning
confidence: 99%